2016
DOI: 10.1016/j.heliyon.2016.e00117
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of lead aprons in blocking radiation − how protective are they?

Abstract: BackgroundDespite the firmly established occupational risk of exposure to X-rays, they are used extensively in spine surgeries. Shielding by lead aprons is the most common protective practice. We quantified the level of their radiation blocking ability in a real-life setting.MethodsSingle-center, prospective, randomized study of adult patients with degenerative lumbar disorders, scheduled to undergo posterior lumbar interbody fusion. Instrumentation was performed in either a robot-assisted, minimally invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 28 publications
0
26
0
2
Order By: Relevance
“…Furthermore, wearing lead protection has been associated with fatigue and orthopadic complaints for laboratory staff [16], although lead aprons block just about one-third of scattered radiation [17]. Given these well-recognized hazards, it is vitally important that zero- or near-zero-fluoroscopic approaches in EP are explored and refined, to minimise risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, wearing lead protection has been associated with fatigue and orthopadic complaints for laboratory staff [16], although lead aprons block just about one-third of scattered radiation [17]. Given these well-recognized hazards, it is vitally important that zero- or near-zero-fluoroscopic approaches in EP are explored and refined, to minimise risks.…”
Section: Discussionmentioning
confidence: 99%
“…It is not just patients who are at risk, but operators too; a growing body of evidence exists implicating radiation exposure in vascular disease [ 13 ], cognitive impairment [ 14 ], and tumours of the brain and neck [ 15 ] in physicians who perform fluoroscopic-guided interventional procedures. Furthermore, wearing lead protection has been associated with fatigue and orthopadic complaints for laboratory staff [ 16 ], although lead aprons block just about one-third of scattered radiation [ 17 ]. Given these well-recognized hazards, it is vitally important that zero- or near-zero-fluoroscopic approaches in EP are explored and refined, to minimise risks.…”
Section: Discussionmentioning
confidence: 99%
“…However, screw placement under fluoroscopic guidance requires more surgical time and carries a risk of radiation exposure for both surgeons and patients, despite the use of protective equipment and devices. Moreover, a recent study demonstrated that lead aprons were less protective than expected 5) . As previously reported in the cadaveric study 15) , free hand insertion technique of S2AI screw could be an alternative method to address these concerns.…”
Section: Discussionmentioning
confidence: 95%
“…Navigation systems have been shown to increase pedicle screw placement accuracy compared to freehand techniques, from about 90-91% to around 95-97% [4,5]. Robotic guidance systems have shown similar or higher levels of accuracy [6,7,20], even when used in MIS procedures and compared to a freehand open approach [8,9,21,23]. In addition, Kim et al showed a decrease in radiation doses to below detectable levels when integrating navigated-assisted fluoroscopy in MIS-TLIF, in contrast to a mean 12.4 mREM radiation dose in open, standard fluoroscopy TLIFs [11].…”
Section: Introductionmentioning
confidence: 99%